Synthesis of PTh/PEDOT Films into FTO Substrate by Electrodeposition, for Energy Storage Systems - Daniel Alejandro Vázquez-Loredo; Ulises Páramo-García; Luis Alejandro Macclesh Del Pino-Pérez; Nohra Violeta Gallardo-Rivas; Ricardo García-Alamilla; Diana Lucia Campa-Guevara (Condensed Matter)
Thin films of monomeric species polythiophene (PTh), poly-(3,4-ethylenedioxythiophene) (PEDOT), and the copolymer PTh/PEDOT were prepared through electropolymerization and deposited above fluorine-doped tin oxide (FTO) substrates. The functional groups of the monomeric species (PTh, PEDOT) and polymeric species (PTh/PEDOT) were characterized by Fourier-transform infrared spectroscopy, while morphological properties were evaluated using scanning electron microscopy, optical microscopy, and atomic force microscopy. The analysis showed that monomers films exhibited less material deposition; otherwise, the copolymer PTh/PEDOT showed better deposition on substrate. In addition, the electrochemical characterization showed that the materials that resulted from copolymerization presented an improvement in electrochemical properties relating to monomer properties. The effect of overoxidation of the monomers applied during the electropolymerization process is also known.